Análise de desempenho da produtividade na aplicação da água residuária de indústria de mandioca em cultivo Brachiaria Brizantha cv. MG-5 - Mariano, Daiane de Cinque (2009)
The reuse of water from food industries of vegetable origin, as a source of water, nutrients and organic matter for soil and plants is a practice traditionally used in the agriculture due to its analogy with the fertirrigation. Among the several waste water applied to the soil, there is the water from the cassava industries. However, its application, as most of the waste water still requests parameters determination and standardization to systematize both agricultural and environmental applications. In this research it was evaluated the effects of the waste water application from cassava industry in Brachiaria brizantha cv. MG-5, with use of a hydraulic sprinkler, having as treatments the total sheets of waste water applied at 5, 10, 20, 25, 30 and 35 meters of distance from the sprinkler. It was applied cassava waste water in the experimental area during 10 weeks, for 4 continuous hours a week, each application, totaling 40 hours of irrigation, from November 20, 2008 to January 30, 2009, when the pasture was cut to 1 cm of height from the soil, weighed its biomass, and collected samples to evaluate its dry mass and content of nutrients in the leaves. The contents of nutrients found in the soil and in the plant of each treatment, as well as the effluent analyses showed that exists correlation between DQO and sheet with the application distance of the waste water by the hydraulic sprinkler. For the dry mass, the angular coefficient of the curve obtained was positive, showing that it increases with the growing sheets of waste water from cassava industry. All of the soil samples analyzed for the depth from 0 to 0.20 and 0.20 to 0.40 m showed low contents of calcium, magnesium, potassium, phosphorus and nitrogen. In the assessment of the plants nutrients contents, only the potassium was with contents above the recommended for grassy.